Halal Supply Chain on Food Products: Evidence From Wali Songo Islamic Boarding School, Ngabar Ponorogo - Iskandar, Oky; Prasetiyo, Luhur; Abdullah, Umar (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2023)
ntroduction: This article aims to describe halal supply chain management implementation at the Wali Songo Ngabar Islamic Boarding School. Halal supply chain management is essential to ensure the halalness of a product, including food products. Research Methods: This research was qualitative-field research. Data was obtained from the management of PT Ngabar Mandiri Sejahtera, boarding school caretakers, and consumers. The data were analyzed using the concept of halal supply chain management. Results: PT Ngabar Mandiri Sejahtera has carried out a halal supply chain management process. These processes are halal procurement, halal manufacturing, halal distribution, and halal logistics. Conclusion: PT Ngabar Mandiri Sejahtera has carried out the halal supply chain management process, although some processes have not been maximized. Some programs to maximize the implementation of halal supply chain management are socialization and educating producers on the importance of halal certification, and facilitating halal certification programs for producers.